Integrating digital citizenship into civic education: a sequential approach to enhancing responsible online behavior in the 21st century - Sarbaini Sarbaini (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study addresses the growing issue of irresponsible online behavior among students in the digital era, which reflects a gap between technological engagement and civic responsibility. The research aims to develop a sequential approach to integrating digital citizenship into civic education to enhance responsible online behavior. This study employs a qualitative library research method, utilizing primary data from relevant scholarly literature and secondary data from books, journals, and research reports related to digital citizenship, civic education, and online behavior. Data were collected through systematic literature review and analyzed using content analysis to identify key patterns and relationships. The findings indicate that a structured, sequential integration—covering awareness, skill development, and application—effectively improves students’ ethical understanding and online conduct. The study concludes that integrating digital citizenship into civic education is essential and provides a practical framework for fostering responsible and informed digital citizens in the 21st century.